Sistem Monitoring Penggunaan Air di Apartemen/Mal MultiTenant dengan NodeMCU dan Raspberry Pi - Albert Ong; Andreas Handojo; Resmana Lim (Jurnal Infra, 2021)
As survey results conducted, it was found that it was difficult tomonitor water consumption and to manage water consumption.Water consumption become very unregulated and the surveyconducted found that respondents agreed with the existence of aweb-based water consumption monitoring and managementsystem. In this study, a trial will be conducted to help solve thisproblem by modernizing water meters or implementing Internetof Things technology on each water meter. Then for paymentsystem will be using a token system. The implementation of IoT inwater meters is in terms of measuring water consumption andlimiting the water consumption. The results of the system foundthat the system was capable of monitoring water consumption,limiting water consumption, and increase water consumptionlimit using token.